Mefloquine pharmacokinetics in pregnant women with acute falciparum malaria. - Na Bangchang, K; Davis, T; Looareesuwan, S; White, N; Bunnag, D; Karbwang, J (1994)
Mefloquine has an established place in the treatment of chloroquine-resistant falciparum malaria. To investigate mefloquine pharmacokinetics in pregnancy, 9 untreated pregnant women aged 16-33 years and 8 non-pregnant females aged 16-38 years received an average of 15 (range 13-19) mg mefloquine/kg body-weight as single-dose treatment for uncomplicated falciparum malaria. Regular blood samples were taken during the subsequent 48 h and then intermittently for 3-26 d after treatment. Whole blood mefloquine concentrations were analysed by high-performance liquid chromatography and a one-compartment open pharmacokinetic model was fitted to the data. Peak mefloquine concentrations were significantly lower in the pregnant patients (median [range]; 1257 [650-1584] vs. 1617 [1051-3111] ng/mL) and the total apparent volume of distribution (Vd/f) was larger (10.8 [8.3-26.1] vs. 10.0 [4.8-13.9] L/kg; P < 0.05 in each case), consistent with an expanded circulating blood volume and increased tissue binding in pregnancy. There was no significant difference between the 2 groups in half-times of absorption or elimination (P > 0.1), and systemic clearance rates were also similar. These results suggest that pregnant patients need larger doses of mefloquine than non-pregnant women to achieve comparable blood levels, an important consideration in areas where multi-drug resistant falciparum malaria is emerging.